PENGARUH PENERAPAN SOFT SKILLS TERHADAP PENINGKATAN KESIAPAN KERJA MAHASISWA JURUSAN KEBIDANAN TINGKAT AKHIR DI POLTEKKES KEMENKES PALU - Niluh Nita (Viva Medika, 2018)
Midwives produced at this time are still not qualified, seen from midwife graduates who are unable to answer the challenges and needs of the community as users in midwifery services. Many graduate midwives have not been in accordance with the profile of graduate midwives who have soft skills. The purpose of this study was to determine the effect of the application of soft skills on improving the work readiness of students at the final midwifery department at the Ministry of Health of the Ministry of Health in Palu. The design of this study used a quasy experiment method with one group pre-post test without control design with a cross sectional approach. The study was conducted at the Department of Midwifery Department, DIII Study Program and D IV Midwifery Midwifery Study Program, Ministry of Health, Ministry of Health, Palu on August 20 to October 31, 2017. The population and sample in this study were final level midwifery students totaling 122 students. How to collect data using a questionnaire sheet. Data analysis compares the results of pretest and posttest. The results of the study showed that there were differences in mean values ​​before the study 55.13 (5.01) and after the study 79.38 (5.37). The percentage of change shows an increase in work readiness as much as 43.07% at the end of the study. Statistical test results obtained ρ value <0.001, which means that ρ value <α. this means that there is an Influence of Soft skills Implementation on Increasing Work Readiness of End-Level Midwifery Students at the Ministry of Health's Polytechnic of Palu. There are influences on the influence of soft skills implementation on increasing work readiness of final-level midwifery students at the Ministry of Health in the Polytechnic of Palu. Suggestions are needed to habituate the application of character education that is carried out in an integrated manner in all educational environments. Keywords: Soft Skill, Work Readiness, Students